Manufacturing and characterization of PIM-W materials as plasma facing materials. (22nd January 2016) - Pintsuk, G; Antusch, S; Rieth, M; Wirtz, M
Abstract: Powder injection molding (PIM) was used to produce pure and particle reinforced W materials to be qualified for the use as plasma facing material. As alloying elements La2 O3, Y2 O3, TiC, and TaC were chosen with a particle size between 50 nm and 2.5 μ m, depending on the alloying element. The fabrication of alloyed materials was done for different compositions using powder mixtures. Final sintering was performed in H2 atmosphere at 2400 °C resulting in plates of 55 × 22 × 4 mm 3 with ∼98% theoretical density. The qualification of the materials was done via high heat flux testing in the electron beam facility JUDITH-1. Thereby, ELM-like 1000 thermal shock loads of 0.38 GW m −2 for 1 ms and 100 disruption like loads of 1.13 GW m −2 for 1 ms at a base temperature of 1000 °C were applied. The obtained damage characteristics, i.e. surface roughening and crack formation, were qualified versus an industrially manufactured pure reference tungsten material and linked to the material's microstructure and mechanical properties.